CONCEPTUALLY-TECHNOLOGICAL APPROACHES IN THE CREATION OF A SINGLE INTEGRATED MEDICAL EDUCATIONAL SPACE - O. P. Mintser (Medična Informatika ta Inženerìâ, 2015)
It was analyzed technological relations of creation a common educational space and a unified educational environment. It has proposed design features a single educational space, including space activity, pertinence and effectiveness of using content in IIES. Typical structure of IIES was described. It consists of three main elements: learning management system, tools for checking (testing) Learning and Management System of the teachers’ activities in the structuring of educational material.